Visual conditions and postural directions affect postural sway variability in patients with Parkinsons disease - Rinaldi,Natalia Madalena (2015)
Postural sway variability was evaluated in Parkinsons disease (PD) patients at different stages of disease. Twenty PD patients were grouped into two groups (unilateral, 14; bilateral, 6) according to disease severity. The results showed no significant differences in postural sway variability between the groups (p >= 0.05). Postural sway variability was higher in the antero-posterior direction and with the eyes closed. Significant differences between the unilateral and bilateral groups were observed in clinical tests (UPDRS, Berg Balance Scale, and retropulsion test; p <= 0.05, all). Postural sway variability was unaffected by disease severity, indicating that neurological mechanisms for postural control still function at advanced stages of disease. Postural sway instability appears to occur in the antero-posterior direction to compensate for the stooped posture. The eyes-closed condition during upright stance appears to be challenging for PD patients because of the associated sensory integration deficit. Finally, objective measures such as postural sway variability may be more reliable than clinical tests to evaluate changes in balance control in PD patients.